Herramientas digitales utilizadas para la evaluación formativa de los aprendizajes por los docentes del bachillerato general unificado de la Unidad Educativa Fiscomisional la Dolorosa en el primer trimestre del año lectivo 2024-2025 - Buri Caraguay, Julissa Yusibeth (2025)
Digital tools encompass all software programs that promote collaborative and dynamic learning. Formative assessment is a continuous, participatory, and contextualized pedagogical process that aims to improve the educational quality of students within the teaching-learning process. Therefore, several digital tools exist to support formative assessment, providing teachers with the means to foster active and collaborative learning among students. Therefore, the present research had the objective: To analyze the digital tools used for the formative evaluation of learning by the teachers of the unified general baccalaureate La Dolorosa high school in the first quarter of the 2024-2025 school year. For which a methodology based on the deductive method, with a quantitative approach, descriptive scope, with a cross-sectional study design was used; consequently, an instrument for collecting information was developed and the survey technique was used, which was applied to thirty teachers of the educational institution taken for the investigation. In relation to the results obtained in the research, it was possible to identify 8 digital tools for formative evaluation through a descriptive table, likewise, it was possible to diagnose the teaching use of digital tools in formative evaluation. To conclude the research, it was possible to analyze that the digital tool Quizizz is the most used, the same one that is located on the usual scale, on the other hand, the Socrative tool is used frequently and EDpuzzle is the one that is never uses, concluding that the most commonly used formative assessment tool is Google Forms by the school's teachers